2008
DOI: 10.1037/0022-3514.95.3.739
|View full text |Cite
|
Sign up to set email alerts
|

Culture, cross-role consistency, and adjustment: Testing trait and cultural psychology perspectives.

Abstract: Trait and cultural psychology perspectives on cross-role consistency and its relation to adjustment were examined in two individualistic cultures, the United States (N = 231) and Australia (N = 195), and four collectivistic cultures, Mexico (N = 199), Philippines (N = 195), Malaysia (N = 217), and Japan (N = 180). Cross-role consistency in trait ratings was evident in all cultures, supporting trait perspectives. Cultural comparisons of mean consistency provided support for cultural psychology perspectives as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
97
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 118 publications
(106 citation statements)
references
References 88 publications
(211 reference statements)
6
97
2
1
Order By: Relevance
“…In addition, in both cultural samples the strongest correlations were observed between cross-role variability and negative affect, as in the present study. Church, Anderson-Harumi et al (2008) found that cross-role consistency predicted well-being better in the United States than in Mexico, the Philippines, Malaysia, and Japan, and cross-role consistency was again most reliably related to negative affect. Finally, two cross-cultural studies examined the relationship between cross-context consistency and alternative indicators of well-being.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In addition, in both cultural samples the strongest correlations were observed between cross-role variability and negative affect, as in the present study. Church, Anderson-Harumi et al (2008) found that cross-role consistency predicted well-being better in the United States than in Mexico, the Philippines, Malaysia, and Japan, and cross-role consistency was again most reliably related to negative affect. Finally, two cross-cultural studies examined the relationship between cross-context consistency and alternative indicators of well-being.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, we define self-concept consistency as the consistency of individuals' trait ratings across different roles, and refer to this construct as cross-role consistency (see also Boucher, 2011;Church, Anderson-Harumi et al, 2008). Others have labeled this construct identity consistency (Suh, 2002), self-concept unity (Campbell et al, 2003), or, inversely, self-concept differentiation (Roberts & Donahue, 1994), cross-role variation (Sheldon, Ryan, Rawsthorne, & Ilardi, 1997), or intraindividual personality variability (Baird, Le, & Lucas, 2006).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…(2010) found that Chinese averaged modestly lower in self-concept consistency across roles than did Americans, and attributed the cultural differences to dialecticism. Church, Anderson-Harumi, et al (2008) concluded that the cultural differences in their study were better explained by East Asian dialecticism than individualism-collectivism, because only their Japanese sample, and not Mexicans, Filipinos, or Malaysians, exhibited lower consistency than their American and Australian samples. Using a different methodology, Kanagawa, Cross, and Markus (2001) had Americans and Japanese fill out a sentence completion measure of self-concept while situated in different contexts.…”
Section: Trait and Cultural Psychology Perspectives On Consistencymentioning
confidence: 99%